Reduction of Adolescent Idiopathic Scoliosis and Improved Z-Axis Alignment of the Entire Spine When Treating a Symptomatic Patient Using a Multidisciplinary Approach: A Case Report - Villa, Juan Jesus; Zhao, Zhiyang; Pan, Weicheng; Guo, Yongfei (Frontiers in Rehabilitation Sciences, 2022)
Abstract. [Background] To present the improvements of both the x-axis and z-axis posture in a young female with adolescent idiopathic, scoliosis suffering from pain complaint as treated with a multidisciplinary approach. [Case presentation] A 15-year-old reported low back pain for several months. Full spine radiographic assessment revealed a cervical kyphosis, forward head translation, a right ribcage translation, a left higher shoulder, and a dextroconvex lumbar scoliosis with a Cobb angle of 23°. The patient was treated with novel ASPINE Systems treatment protocols incorporating posture exercises, muscle balancing exercises, spinal 3D traction, and spinal manipulation. [Results] Assessment after 50 treatments sessions over a period of 32 weeks revealed a dramatic improvement in postural distortions. The cervical kyphosis reduced by 9°, and was accompanied by a reduction in forward head posture, centering of the thoracic spine, leveling off her shoulders, and a reduction in the dextroconvex scoliosis of 10°. The low back pain was relieved. [Conclusion] A reduction of postural distortions including idiopathic adolescent scoliosis resulted from a multidisciplinary approach utilizing ASPINE Systems.